Microscopic and Molecular Characterization of the Prehaustorial Resistance against Wheat Leaf Rust (Puccinia triticina) in Einkorn (Triticum monococcum) - Serfling, Albrecht; Templer, Sven E.; Winter, Peter; Ordon, Frank (Frontiers in Plant Science, 2016)
Puccinia triticina f. sp. tritici (Eriks.), the causal agent of leaf rust, causes substantial yield losses in wheat production. In wheat many major leaf rust resistance genes have been overcome by virulent races. In contrast, the prehaustorial resistance (phr) against wheat leaf rust detected in the diploid wheat Einkorn (Triticum monoccocum var. monococcum) accession PI272560 confers race-independent resistance against isolates virulent on accessions harboring resistance genes located on the A-genome of Triticum aestivum. Phr in PI272560 leads to abortion of fungal development during the formation of haustorial mother cells and to increased hydrogen peroxide concentration in comparison to the susceptible accession 36554 (Triticum boeoticum ssp. thaoudar var. reuteri). Increased peroxidase and endochitinase activity was detected in PI272560 within 6 h after inoculation (hai). Comparative transcriptome profiling using Massive Analysis of cDNA Ends (MACE) in infected and non-infected leaves detected 14220 differentially expressed tags in PI272560 and 15472 in accession 36554. Of these 2908 and 3004, respectively, could be assigned to Gene Ontology (GO) categories of which 463 were detected in both accessions and 311 were differentially expressed between the accessions. In accordance with the concept of non-host resistance in PI272560, genes with similarity to peroxidases, chitinases, β-1,3-glucanases and other pathogenesis-related genes were up-regulated within the first 8 hai, whereas up-regulation of such genes was delayed in 36554. Moreover, a Phosphoribulokinase gene contributing to non-host resistance in rice against stripe rust was exclusively expressed in the resistant accession PI272560. Gene expression underpinned physiological and phenotypic observations at the site of infection and are in accordance with the concept of non-host resistance.